2012
DOI: 10.3109/11038128.2012.727864
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapists' experiences in integrating a new intervention in collaboration with a researcher

Abstract: One conclusion is the importance of providing opportunities for creating dialogues among researcher and practitioners to narrowing the gap between research and "everyday practice of occupational therapy".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 23 publications
4
26
0
5
Order By: Relevance
“…However, we cannot be sure that all OTs in the CADL group fully implemented the CADL intervention all the time throughout the study. It has been reported that OTs delivering interventions in a research context might find it challenging and report lack of time and experience to apply the research as intended (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot be sure that all OTs in the CADL group fully implemented the CADL intervention all the time throughout the study. It has been reported that OTs delivering interventions in a research context might find it challenging and report lack of time and experience to apply the research as intended (34).…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve sustainable change in behavior, reflection, feedback and application of work methods, routines and roles are necessary (43). In a previous study (10), the importance of reflection as part of the process was found while OTs were active in the implementation of the new intervention. When participating in a workshop with the researcher, the OTs could describe their experiences of intervention with others (colleagues and researchers), as well as the OTs could describe expectations and reconnections to the previous experiences of interacting with clients.…”
Section: Occupation Change Process and Identitymentioning
confidence: 99%
“…Initially the OTs had expectations for access to a tool that could provide support in their meeting with the client based on the client-centered approach. Additional findings were that the OTs felt that previous clinical knowledge and experience were confirmed, but also the skepticism of the new knowledge would not be possible to integrate into the daily work (10).…”
Section: Introductionmentioning
confidence: 99%
“…To be given the opportunity for clinicians to translate their knowledge is an important component in the process of change when implementing evidence in clinical practice [36]. A previous study [37] of clinicians' attitudes towards evidence-based practice (EBP) [10] and their experiences of collaborating with researchers indicated that the participating OTs experienced both an expectation and a skepticism to whether or not that knowledge would assist them to change their clinical practice. However, by participating in a research project they received confirmation of their previous knowledge, which facilitated the implementation of the new intervention [37].…”
Section: Supporting Ots' Acquisition Of Complex Clinical Skillsmentioning
confidence: 99%
“…A previous study [37] of clinicians' attitudes towards evidence-based practice (EBP) [10] and their experiences of collaborating with researchers indicated that the participating OTs experienced both an expectation and a skepticism to whether or not that knowledge would assist them to change their clinical practice. However, by participating in a research project they received confirmation of their previous knowledge, which facilitated the implementation of the new intervention [37]. The value of the researcher providing the 'right' research evidence consistent with the needs in clinical practice was confirmed in this present study underlining the importance of considering and showing respect for the practitioners' role and clinical experiences are also in line with i-PARIHS [8].…”
Section: Supporting Ots' Acquisition Of Complex Clinical Skillsmentioning
confidence: 99%